Coexpression of an unusual form of the EWS–WT1 fusion transcript and interleukin 2/15 receptor βmRNA in a desmoplastic small round cell tumour. Issue 10 (4th October 2006) - Nakanishi, Y; Oinuma, T; Sano, M; Fuchinoue, F; Komatsu, K; Seki, T; Obana, Y; Tabata, M; Kikuchi, K; Shimamura, M; Ohmori, K; Nemoto, N
Abstract : Background: The β chain of the interleukin 2/15 receptor (IL-2/15Rβ) is induced by the expression of the EWS–WT1 . A case of desmoplastic small round cell tumour (DSRCT) expressing only an unusual EWS-WT1 treated by us is reported here. Aim: To characterise an unusual form of EWS–WT1 . Methods: Frozen tissue sections of the axillary tumour were examined using a laser-assisted microdissection technique and reverse transcriptase polymerase chain reaction. Results: The novel fusion of exon 8 of EWS and the defective exon 10 of WT1 (− KTS ) was detected. Although it was an unusual form, the coexpression of the present EWS–WT1, IL-2/15Rβ and Janus kinase ( JAK1 ) mRNA was detected in the tumour cells. IL-2 and signal transducers and activators of transcription ( STAT5 ) mRNA were detected in both tumour and stromal cells. Conclusion: The induction of the IL-2/15 receptor signalling pathway may contribute to tumorigenesis in DSRCT through a paracrine or an autocrine system, even though the EWS–WT1 was an unusual form.